Facts about Potassium - R. Elaine Turner; Linda B. Bobroff (EDIS)
FCS8805, a 2-page fact sheet by R. Elaine Turner and Linda B. Bobroff, covers the importance of potassium, its functions in the body, and its relationship to blood pressure. Also includes information on how much is needed and how much is in some common foods. Published by the UF Department of Family, Youth and Community Sciences, November 2006.